An evaluation of traceability approaches to support software evolution - Rochimah, S.; Kadir, W. M. N. W.; Abdullah, Abdul Hanan (2007)
Requirements traceability is becoming increasingly significant element in software engineering. It provides critical function in the development and maintenance of a software system. From the software evolution point of view, requirements traceability plays an important role in facilitating software evolution. Since the evolution is inevitable, a traceability approach must take as much as possible the important influencing aspects into account to the evolution processes in order to minimize the evolution efforts. This paper evaluates several recent traceability approaches published in literature with the focus on their contributions to software evolution. The evaluation results may be used as a basis for improving requirements traceability approaches that may simplify the software evolution tasks.